Panteleimon Kulish’s symbolic imagery in comparison to the cristian and mythological archetypal symbolism (based on the story “Granny from the other world”) - Кравченко, Наталія Кимівна (НУБіП України, 2019)
The paper focuses on the symbolic imagery of the P. Kulish’s story “Granny from the other World” in the framework of its relation to the fairy tale / mythological and Christian word pictures. The research aims at identifying the symbolic images of the Kulish‟s story in their comparison to Christian and mythological concepts while undertaking the images‟ comparative semiotic and archetypal analysis. To achieve the purpose, we have applied the methodology composing of the methods of archetypal analysis, text and contextual interpretation analysis, elements of the structural-narrative, stylistic and comparative analysis.
Волічна образність текстів Пантелеймона Куліша у порівнянні з християнською і міфологічною архетипною символікою (на матеріалі оповідання «Бабуся з того світу»)
У статті висвітлюється символічна образність твору П. Куліша «Бабуся з того світу» у її співвіднесенні з казковою / міфологічною та християнською картинами світу. Дослідження спрямоване на виявлення символічних образів наративу в аспекті їх порівняння з християнськими та міфологічними концептами із залученням семіотичного та архетипного аналізу образів. Для досягнення зазначеної мети застосовано методологію, що включає методи архетипного аналізу, інтерпретації тексту, контекстуального аналізу, елементи структурно-наративного, стилістичного та порівняльного аналізу.
Keywords: symbolic images; Panteleimon Kulish; Christian; mythological; archetype; символічні образи; Пантелеймон Куліш; християнський; міфологічний; архетип